1993
DOI: 10.1073/pnas.90.8.3549
|View full text |Cite
|
Sign up to set email alerts
|

VirA, the plant-signal receptor, is responsible for the Ti plasmid-specific transfer of DNA to maize by Agrobacterium.

Abstract: Agrobacteria exhibit marked Ti (tumorinducing)/Ri (root-inducing) plasmid specificity in their interaction with the Gramineae. In this study, we have used the technique of "agroinfection," in which Agrobacterium-mediated delivery of viral genomes into plants is detected by the development of viral disease symptoms, to identify the region of the Ti plasmid which is responsible for the major differences seen in the ability of nopaline-vs. plants (4, 5). However, more recent work reported that certain monocotyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…pJD102W was constructed as follows: a PstI site was introduced into the C58 virA gene of pDR169 (38) by changing thymine to cytosine at position 717 in the coding sequence and guanine to cytosine at position 720 by means of PCR amplification. The mutations were confirmed by DNA sequencing using the Sequenase version 2.0 kit according to the instructions provided by the manufacturer (United States Biochemical).…”
Section: Methodsmentioning
confidence: 99%
“…pJD102W was constructed as follows: a PstI site was introduced into the C58 virA gene of pDR169 (38) by changing thymine to cytosine at position 717 in the coding sequence and guanine to cytosine at position 720 by means of PCR amplification. The mutations were confirmed by DNA sequencing using the Sequenase version 2.0 kit according to the instructions provided by the manufacturer (United States Biochemical).…”
Section: Methodsmentioning
confidence: 99%
“…11;Leroux et al 1987;Porter et al 1987;Christie et al 1988;Jin et al 1990c;Kuldau et al 1990;Shirasu et al 1990). virA and virG encode a histidine protein kinase and the cognate response regulator, two components of a signal transduction device that al-lows Agrobacteria to respond to specific plant signals by expressing virulence genes (Jin et al 1990a,b,c;Raineri et al 1993). VirD1-3 fulfill an analogous function as TraHIJ with VirD2 being linked to the cleaved T-DNA (Yanofsky et al 1986;Herrera-Estrella et al 1988;Ward and Barnes 1988;Young and Nester 1988;Howard et al 1989).…”
Section: Type IV Secretionmentioning
confidence: 99%
“…DNA sequencing reactions were initiated on both strands by using M13 forward and reverse primers. The C58 virA sequence, used in comparative analyses, was as reported by Rogowski et al (39) and, when useful, confirmed by examination of the C58 virA sequence of pDR169 (37).…”
Section: Methodsmentioning
confidence: 74%